Dampak penggunaan warna panas dalam upaya branding suatu produk - Gamaliel Bharoto Adi (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2017)
In the design world, all elements can influence the product to be better or vice versa. One element in the world of design is color. The use of color can be an ideal weapon but vice versa. This articlediscusses the correlation between the use of hot color with the branding effort of a product. It is discussed on how a color scheme is able to give a certain impression and character to a product. This study aims to investigate the right color as a branding effort of a product. This research is done by collecting data in literature. The research findings show that the color is able to give the impression in accordance with the psychology of color and able to give character to the product.Keywords: color, hot, product, branding